Acute Coronary Syndrome after 17 Years of Bare Metal Stent Implantation: “Very” Very Late Stent Thrombosis - Raghavendra Rao K; S. Reddy; J. R. Kashyap; K. Vikas; Hithesh Reddy; Vadivelu Ramalingam (Case Reports in Cardiology)
Very late stent thrombosis (VLST) is a catastrophic and life-threatening complication after percutaneous coronary intervention which presents as an acute coronary syndrome with significantly high mortality and morbidity. VLST is a rare entity with drug-eluting stents and even rarer with bare metal stents. The exact pathophysiologic mechanism of VLST after BMS implantation is not known although various mechanisms have been proposed. Recently, in-stent neoatherosclerosis with intimal plaque rupture has been proposed as a potential mechanism of VLST after BMS. We report a rare case of VLST occurring 17 years after BMS implantation with angiographic and intravascular imaging evidence which provides insight into the mechanisms of VLST.